Verificação, em condiçoes naturais, da infecção de mais três hematófagos (Anophelineos, Flebótomos e Simulídeos) em leprosos Verification, in natural conditions, of infection of more three hematophagi (Anopheline, Flebotomus and Simulidae) in lepers - H. C. de Souza-Araujo (Memorias do Instituto Oswaldo Cruz, 1943)
The A. went last August to the State of Minas Gerais to continue his studies on transmission of leprosy by insects. He selected ten lepers (all L3 cases) for his experiments. It happened in the middle of August, a few day after freezing temperature. Practically there were no day mosquitoes, even near a river where in March there were very many. Bringing the patients to a wood, near the Peixe River (Fish River), at the dawn they were attacked by very many Anopheles, some flebotomus, a few Simulium and very rare Culex scapularis. All these insects became infected, in different degrees, by biting such patients. CONCLUSIONS. 1. Two species of Anopheles (A. albitarsis and A. tarsimaculatus) became strongly infected by Hansen bacilli. 2. By dissection done by Dr. Oliveira Castro were found lepra bacilli in various points of the proboscis of two Flebotomus (F. intermedius) and in their stomachs. 3. By smearing were found lepra bacilli in two specimens of Simulium sp. (probably pertinax). 4. It was confirmed also the verification done last March, at the same Leper Colony, that Phthirius pubis can be also a carrier of lepra bacillus. 5. There was confirmed also natural infection of nymphs of Amblyomma cajennense in lepers. Dr. Oliveira Castro is dissecting the Anopheles to locate the bacilli in their organisms and he started, with the cooperation of the Director of Colonia Santa Fé, Dr. José Mariano, attenpts to re-infect a group of negative-nerve cases of leprosy with infected mosquitoes.